Human Capital, Economic Education, and Economic Growth: A Multi-Dimensional Analysis of Development Pathways in Emerging Economies - Iqbal Shaukat (CV. Sakura Digital Nusantara, 2025)
Economic growth is widely recognized as a long-term and cumulative process shaped by institutional quality, human capital, and the effectiveness of national economic systems. While previous studies focus heavily on macroeconomic indicators, this research highlights the interconnected roles of economic education and human resource development as foundational drivers of sustainable growth. This study employs a qualitative descriptive design supported by structured questionnaires and semi-structured interviews involving accountants, tax consultants, teachers, business actors, students, and economists to examine perceptions of the importance of economic education and taxation literacy. The findings show strong consensus across professional groups that economic education enhances societal understanding of national income, consumer prices, taxation systems, and development policies. Moreover, human resource development particularly through training, technical skills, and organizational support emerges as a significant contributor to economic performance and institutional stability. The study concludes that economic education and human resource capabilities function not only as supporting components of growth but as central mechanisms that strengthen fiscal capacity, improve public policy compliance, and enable long-term development. The novelty of this research lies in integrating economic education, taxation literacy, and human resource development into a unified framework explaining how knowledge-based capacities accelerate economic progress in emerging economies.